A randomized controlled trial of real versus sham acupuncture for basal thumb joint arthritis. (June 2020) - Barnard, Anna; Jansen, Victoria; Swindells, Mark G.; Arundell, Melanie; Burke, Frank D.
We report a single-blinded randomized controlled trial comparing acupuncture to sham (non-penetrating) needling for relief of symptoms of basal thumb joint arthritis. Seventy acupuncture naive patients with basal thumb joint arthritis were randomized to receive true acupuncture or sham needling with 35 patients in each arm. Blinded baseline and post-treatment assessments included visual analogue pain scores for different grips and movement. Function was assessed using the Nelson questionnaire. Both groups showed statistically and clinically significant improvements in pain at week one post-treatment compared with baseline, but there was no difference between the treatment groups. The pain relief was comparable with published data for some standard treatments. Acupuncture did not perform better than sham needling in this study, indicating that pain relief may have been achieved through non-specific mechanisms. Level of evidence: I